Non-AIDS comorbidity burden differs by sex, race, and insurance type in aging adults in HIV care. (1st December 2019) - Palella, Frank J.; Hart, Rachel; Armon, Carl; Tedaldi, Ellen; Yangco, Bienvenido; Novak, Richard; Battalora, Linda; Ward, Douglas; Li, Jun; Buchacz, Kate
Abstract : Objective: To understand the epidemiology of non-AIDS-related chronic comorbidities (NACMs) among aging persons with HIV (PWH). Design: Prospective multicenter observational study to assess, in an age-stratified fashion, number and types of NACMs by demographic and HIV factors. Methods: Eligible participants were seen during 1 January 1997 to 30 June 2015, followed for more than 5 years, received antiretroviral therapy (ART), and virally suppressed (HIV viral load <200 copies/ml ≥75% of observation time). Age was stratified (18–40, 41–50, 51–60, ≥61 years). NACMs included cardiovascular disease, cancer, hypertension, diabetes, dyslipidemia, arthritis, viral hepatitis, anemia, and psychiatric illness. Results: Of 1540 patients, 1247 (81%) were men, 406 (26%) non-Hispanic blacks (NHB), 183 (12%) Hispanics/Latinos, 575 (37%) with public insurance, 939 (61%) MSM, and 125 (8%) with injection drug use history. By age strata 18–40, 41–50, 51–60, and at least 61 years, there were 180, 502, 560, and 298 patients, respectively. Median HIV Outpatient Study observation was 10.8 years (range: min-max = 5.0–18.5). Mean number of NACMs increased with older age category (1.4, 2.1, 3.0, and 3.9, respectively; P < 0.001), as did prevalence of most NACMs ( P < 0.001). Age-related differences in NACM numbers were primarily due to anemia, hepatitis C virus infection, and diabetes. Differences (all P < 0.05) in NACM number existed by sex (women >men, 3.9 vs. 3.4), race/ethnicity (NHB >non-NHB, 3.8 vs. 3.4), and insurance status (public >private, 4.3 vs. 3.1). Conclusions: Age-related increases existed in prevalence and number of NACMs, with disproportionate burden among women, NHBs, and the publicly insured. These groups should be targeted for screening and prevention strategies aimed at NACM reduction. Abstract : Supplemental Digital Content is available in the text